2017
DOI: 10.4238/gmr16019529
|View full text |Cite
|
Sign up to set email alerts
|

Direct effects on scenarios and types of path analyses in corn hybrids

Abstract: ABSTRACT. The objective of this study was to estimate the direct effects of explanatory variables on the grain yield of corn in the combinations formed by three types of hybrids x two harvests x nine scenarios of explanatory variables x two types of path analyses. Eleven explanatory variables were measured in 361, 373, and 416 single-, triple-, and double-cross hybrid plants from the 2008/2009 harvest, respectively, and in 1777, 1693, and 1720 single-, triple-, and doublecross hybrid plants from the 2009/2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(33 reference statements)
0
3
0
1
Order By: Relevance
“…1 Heritability impacts of traits on the selection have been studied, showing that predictive models work relatively well, even for low-heritability traits (TOEBE et al, 2017). Grattapaglia and Resende (2011) reported that the accuracy increased by only 10-20% as the heritability increased from 0.2 to 0.6, regardless of the population size, indicating greater individual selection gains even for low-heritability traits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Heritability impacts of traits on the selection have been studied, showing that predictive models work relatively well, even for low-heritability traits (TOEBE et al, 2017). Grattapaglia and Resende (2011) reported that the accuracy increased by only 10-20% as the heritability increased from 0.2 to 0.6, regardless of the population size, indicating greater individual selection gains even for low-heritability traits.…”
Section: Resultsmentioning
confidence: 99%
“…Grattapaglia and Resende (2011) reported that the accuracy increased by only 10-20% as the heritability increased from 0.2 to 0.6, regardless of the population size, indicating greater individual selection gains even for low-heritability traits. According to Toebe et al (2017), tests with high selection accuracy present lower residual variance and greater genetic variance.…”
Section: Resultsmentioning
confidence: 99%
“…No studies with rye crop in which diagnoses were made by CN or DET were found. In other crops, low degree of multicollinearity was observed in sunflower traits (CN = 9.64) (FOLLMANN et al, 2019) and severe multicollinearity was observed in morphological traits of showy rattlepod (CN = 1,113.08) (TOEBE et al, 2017a) and maize hybrids (CN > 1,000) (TOEBE; CARGNELUTTI FILHO, 2013;OLIVOTO et al, 2017b;TOEBE et al, 2017b). The DET was used for the diagnosis in maize traits using all observations (DET = 3.02×10 -6 ) and mean values of plots (DET = 1.26×10 -7 ) (OLIVOTO et al, 2017b).…”
Section: Resultsmentioning
confidence: 99%
“…(1) MFP: massa fresca de parte aérea; MSP: massa seca de parte aérea da planta; NSE: número de espiguetas espiga -1 ; NGE: número de grãos espiga -1 ; NGS: número de grãos espigueta -1 ; MGP: massa de grãos planta -1 ; M100: massa média de 100 grãos, em gramas. (TOEBE et al, 2017c).…”
Section: Methodsunclassified